PENGARUH KARTU â€œSIKSAKLaKâ€ DAN PENGGUNAANNYA TERHADAP KEMAMPUAN MENULIS SISWA SMA PERINTIS BANDAR LAMPUNG - Rifnida, Rifnida; Anggraini, Tri Riya (Lentera: Jurnal Ilmiah Kependidikan, 2019)
This study aims to determine whether there is an effect of the SIKSAKLak card and its use on the writing ability of the Class X Pioneers of Bandar Lampung High School students, describing the influence of the use of SIKSAKLak cards on writing skills. The method used is a quasi-experimental method. The sample of this study was 60 students with details of 30 students in class X1 (experimental group) and 30 students in class X2 (control class). The technique used in collecting data is a test technique, while the data analysis technique uses the t test with the help of the SPSS 20 computer program. The results showed that there were differences in test results between the experimental group and the control group. The average initial test score for the experimental group was 62.81 and the control group was 58.61. The final test average score of the experimental group was 75.00 and the control group was 65.23. This shows that there is an influence of the use of SIKSAKLak cards on writing skills in class X of Bandar Lampung Pioneer High School. Thus Ha which reads "There is a difference in the ability to write students who are taught using SIKSAKLak cards with students who are taught without using SIKSAKLak cards" accepted.